Subtle Bodies, Wrathful Deities and Men in Buddhist Tantric Traditions - Child, Louise (Religions of South Asia, 2007)
Combining fearsome images, ‘magical’ rites of subjugation and challenging portrayals of sexuality, wrathful deities appear to epitomize all that makes tantric Buddhism distant from early Buddhism’s traditional orientations. On one level, this distance can be attributed to processes of incorporation of ‘demonic’ elements from other indigenous religious traditions. Drawing from the theoretical perspectives of Durkheim and Mauss, however, I will argue that it is precisely this motif of ‘incorporation’ that not only gives wrathful deities their distinctive potency, but also positions them at the centre of the ambivalence that is tantric Buddhism. While the tantric Siddha, in common with Mauss’s magician, incorporates bodily leavings and peripheral rites, he also, I suggest, absorbs and negotiates potentially poisonous emotional states such as terror and anger through the medium of the subtle body, thereby forming a model of masculinity that is both a defining force within tantric Buddhism and suggestive of further investigation within anthropological studies of male cultures more broadly.